Barriers to Eastern Oyster Aquaculture Expansion in Virginia - Beckensteiner, Jennifer; Kaplan, David M.; Scheld, Andrew M. (Frontiers in Marine Science, 2020)
The eastern oyster once provided major societal and ecosystem benefits, but these benefits have been threatened in recent years by major declines in oyster harvests. In many areas, recovery of oyster aquaculture faces significant societal opposition and spatial constraints limiting its ability to meet expectations regarding future food needs and provision of ecosystem services. In Virginia, oyster aquaculture has begun to rebound, concurrent with an increase in subaqueous leased areas (over 130,000 acres of grounds are currently leased). Though private leases must in theory be used for oyster production, in practice, they can be held for other reasons, such as speculation or intentional exclusion of others. These factors have led to large variation over time and space in the use of leases in the lower Chesapeake Bay, and privately leased grounds are now thought to be underutilized for oyster production. This research examined potential barriers to expansion of oyster aquaculture in Virginia. We first evaluated if a lack of space was limiting industry expansion and quantified temporal and spatial trends in the use and productivity of leases. Then, differences in used and non-used leases were investigated in relation to variables thought to be related to “not in my backyard” attitudes, congestion, speculation, local economic and environmental conditions. Finally, the performance of the Virginia leasing system was compared with those in other states along the U.S. East and Gulf Coasts. We found limited evidence of spatial constraints though strong evidence of social and regulatory inefficiencies. While rates of lease use increased from 2006 to 2016, only 33% of leases were ever used for oyster production and about 63% of leaseholders reported no commercial harvests. Non-used leases tended to be smaller, and were found in more populated, high-income regions, consistent with both speculative and exclusionary uses. Virginia was found to have the lowest levels of total production of cultured oysters per leased acre among the states of the eastern U.S. These results indicate that there is room for oyster aquaculture expansion in Virginia if societal, regulatory and economic barriers can be reduced or if existing leased areas are used more efficiently.